Outcome of Triamcinolone Injection following Optical Internal Urethrotomy in Short Segment Anterior Urethral Stricture (IAHS Medical Journal, 2024)
Background: Internal Urethrotomy is a surgical procedure to treat urethral stricture disease. To assess the outcome of triamcinolone injection following Optical Internal Urethrotomy (OIU) in short segment anterior urethral stricture in our setting.Materials and methods: This randomized controlled trial was carried out in the Department of Urology, Chittagong Medical College Hospital, Chattogrm from September 2017 to August 2018 on 60 patients with short segment of anterior urethral stricture. Cases were randomly allocated to group A (OIU with Triamcinolone) and group B (OIU without Triamcinolone). Each group consisted of 26 patients. Data were analyzed and compared by Stata (version 16).Results: There were no significant differences in the baseline characteristics of the patients. At 9 months of follow up, American Urological Association Symptom Score (AUA score) was decreased in Group A (5.8±4.3) in comparison to control Group B (10.4±7.9). In Group A, Qmax of only 1 patient was < 15 ml/min which was presented at 9 month of the study period. This was considered as recurrence (3.57%). So, success rate of Group A was 96.43% as the Qmax of the 27 patients were > 15ml/min. In Group B, Qmax of the 4 patients (14.81%) were found